Tubular ileal duplication causing small bowel obstruction in a child - SK Sekendar Ali, MBBS, MS; Narendra Nath Mukhopadhyay, MBBS,MS,Mch (Elsevier, 2022)
Background: Gastrointestinal duplications are rare congenital abnormalities that has been rarely reported, accounting for 0.01% of live births cases. Despite medical tests and radiological examinations, the diagnosis could be made during the operation. It is difficult to diagnose and prime to be aware of variants, manage such challenging case in emergency setting. Case presentation: We present a case of 9 yrs old girl child, Patient with duplication of gastrointestinal tract (ileal-tubular type) presenting as acute intestinal obstruction who underwent an exploratory laparotomy and resection -anastomosis done. Conclusions: The initial diagnosis and surgical management of such patient is challenging due to very rare congenital anomalies and atypical presentation in emergency setting. A high index of suspicion is required for diagnosis. It is important to be aware that common presentations in the emergency room like intestinal obstruction, perforative peritonitis and complicated appendicitis may be manifestations of an underlying enteric duplication cyst when another more common source cannot be identified.